Pro dan Kontra dalam Perkuliahan Secara Blended Learning di Program studi Pendidikan Matematika UNU Pasuruan Tahun 2023 - Achmad Firmansyah; Siti Nur Dianah; Agus Qowiyuddin (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
Blended learning is a new learning strategy that provides many benefits for students, as well as a form of information and communication technology support towards new learning modes. This research aims to find out: 1) The pros and cons of blended learning lectures in the UNU Pasuruan mathematics education study program in 2023. 2) supporting and inhibiting factors for the blended learning lecture process. This type of research is qualitative with a descriptive approach. The number of samples in this study was 6. The data collection technique was to include the results of interviews that had been conducted accompanied by documentation of their implementation.